Computer Programming Teachers’ Challenges for Promoting Students Regulation on Flipped Learning Activities during COVID-19 - Anderson Cavalcante Gonçalves; Deller James Ferreira; Valdemar Vicente Graciano Neto (Revista Diálogo Educacional, 2021)
The challenges for computer programming teachers are great, it is difficult to teach concepts and structures inherent in the programming language to students in introductory courses in the field of computer science. The coronavirus pandemic, COVID-19, intensified these difficulties as the entire teaching and learning process migrated to online platforms. The research aims to provide evidence regarding the difficulties that computer science teachers are having to implement inverted classes. The analysis involves the knowledge of teachers’ perceptions of collaborative teaching methods of problem solving, and with regulatory strategies to motivate students and promote reflections on their learning. The results indicate that teachers have had significant difficulties in understanding the use of active methodologies, also in understanding the learning students’ profiles and how they can prepare, plan, implement and favor learning.